Optimasi Produksi Inulinase oleh Khamir Pichia manshurica DUCC Y-015 pada Tepung Umbi Dahlia (Dahlia variabilis Willd.) dengan Variasi Konsentrasi K2HPO4 dan Waktu Inkubasi - Amedia, Inggrit; Wijanarka, Wijanarka; Purwantisari, Susiana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Sugar national supply more and more decreases and can not meet the market needs. The research has been done to find alternative natural sweeteners including inulin from dahlia tubers (D. variabilis Willd). Dahlia tuber can produce 95% of yield of fructose syrup in an enzimatic reaction by inulinase (E.C.3.2.1.7). Inulinase is inductive enzyme that can be produce by P. manshurica. The production of fructose needs to be optimized to get optimum product. The optimization can be done by modifying the nutrient content in the medium such as K2HPO4 and variation of incubation time. The purpose of this study is to determine the concentration of K2HPO4 and optimum incubation time for P. manshurica. This research was conducted in Microbiology Laboratory, Biology Department, Faculty of Science and Mathematics Undip. The examined variable is the growth of yeast cell, inulinase activity, invertase, and the I/S ratio. This research was conducted experimentally using Randomized Complete Block Design (RCBD) factorial pattern with 2 factors, the first factor was the concentration of K2HPO4 (P), with concentrationÂ level (g/L) of 0.5 (P1), 1.0 (P2), and 1.5 (P3). The second factor was incubation time (W) with 12 hours (W12), 18 hours (W18), and 24 hours (W24). Every treatment was repeated three times. The collected data were analyzed using ANOVA. If there was a treatment effect, it will be continued with Duncan test on 5% significance level. The result of analysis show that the highest cell growth and the maximum production of inulinase enzyme was in P3W24 occurs in P3W24 (K2HPO4 1.5 g/L and 24 hours incubation time) treatment at 0.428 IU, but efficient in P1W12 treatment as much as 0.365 IU.Â Keywords: Dahlia variabilis Willd., Inulinase, K2HPO4, Pichia manshurica DUCC Y-015, incubation time